STRATEGI PENGEMBANGAN PERTANIAN PADI ORGANIK DI KABUPATEN HULU SUNGAI SELATAN - Isna Arianti Arianti; Danang Biyatmoko; Rizqi Puteri Mahyudin; Hesty Heryani (EnviroScienteae, 2022)
As a continuation of “Go organic 2010”, Government through Ministry of Agriculture of The Republic of Indonesia has target “1,000 Agriculture Organic Villages” (Directorate General of TP of Indonesian Ministry of Agriculture, 2015). Needs of healthy food is increased along with awareness of the Public and development of healthy life style trend is growing at this moment, so that development of the organic rice agriculture becomes very strategic. Opportunity of organic rice agriculture starts being concerned by farmers in the regency of Hulu Sungai Selatan, the local government has attempted supports through the programs and activities. Organic rice agriculture in the Hulu Sungai Selatan regency has still not yet developed widely, thus, it is required appropriate development strategy with condition and state of the farmers in Hulu Sungai Selatan Regency. Research objectives 1) Analyzing Perceived Value (NP) from the economic, technical and social perception of the community towards the application of the organic rice agricultural system. 2) Identifying and analyzing internal and external faktors that influence in the development of the organic rice agricultural system in Hulu Sungai Selatan Regency. 3) Formulating strategy of organic rice agricultural system in Hulu Sungai Selatan Regency. This study was held on March 2022 in the Gambah Dalam Barat Village in Regency of Hulu Sungai Selatan, South Kalimantan Province.  There were 44 research samples which consisted of 37 farmers and 7 key persons (key informants) and also consisted of formal and informal figures. To analyze the value of perception, Likert scale was used. The identification of internal and internal faktors also used IFAS matrix, EFAS matrix and IE matrix. SWOT matrix was also used to get alternative development strategy and QSPM matrix was used to determine focus strategy in the development of organic rice agricultural system in Hulu Sungai Selatan Regency. Study results show that the perception value of the farmers which was seen from economical perception is on high category (77.92 %), technical perception is on very high category (81.24%) and social perception is (83.71%) on very high category. It shows that awareness and understanding about organic rice agriculture is already very good (positive). IFAS value is 2.755 and EFAS is 3.242. Strength faktor is (1.766) which is more dominant of the weakness faktor (0.989) and the opportunity faktor (2.269) is bigger than threat (0.973). Based on IE matrix, condition of organic rice agricultural system in Hulu Sungai Selatan Regency is located on cell II, possible strategies to be conducted is growing and building strategy which utilize external faktors (using opportunity and facing threat) to overcoming internal faktors (maximizing strength and minimizing weakness) that is enhancing production, developing products, penetrating market, developing market, integrating vertical and horizontal integration. On SWOT matrix is obtained nine alternative strategies and through QSPM matrix has been determined focus strategies include: increasing activity of counseling and accompaniment by officers in the field with value of 16,83869. This strategy is very suitabel because to develop organic rice agriculture, farmers must be always accompanied and helped to apply the system. Value of economical, technical and social perception about organic rice agriculture as adoption initial stage of organic rice agriculture is already very good, some are already on try-out step and next evaluation is just how they can apply and survive in organic rice agricultural system so that the system can develop and development objectives can be achieved.